2021
DOI: 10.3389/fncel.2021.681066
|View full text |Cite
|
Sign up to set email alerts
|

Begonia—A Two-Photon Imaging Analysis Pipeline for Astrocytic Ca2+ Signals

Abstract: Imaging the intact brain of awake behaving mice without the dampening effects of anesthesia, has revealed an exceedingly rich repertoire of astrocytic Ca2+ signals. Analyzing and interpreting such complex signals pose many challenges. Traditional analyses of fluorescent changes typically rely on manually outlined static region-of-interests, but such analyses fail to capture the intricate spatiotemporal patterns of astrocytic Ca2+ dynamics. Moreover, all astrocytic Ca2+ imaging data obtained from awake behaving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…To accurately capture Ca 2+ dynamics in sub-cellular compartments, there is a need to adopt imaging techniques with improved resolution and to develop tools for efficient analysis in three-dimensional (Bindocci et al, 2017;Romanos et al, 2019). Because of our poor understanding of functional compartments, analysis of astrocytic Ca 2+ dynamics has been moving toward state-of-the-art event-based analysis (Romanos et al, 2019;Wang et al, 2019;Bjørnstad et al, 2021), nevertheless ROI (regionof-interest) based analysis, informed by cellular anatomy (functional compartments) and molecular architecture, has been critical for understanding neuron physiology (e.g., spines and boutons). To this end, the identification of morphologically distinct subcellular compartments are promising targets for classical ROI based analysis, i.e., "glial microdomains" on Bergmann glial processes (Grosche et al, 1999) and "astrocytic compartments" on major branches (Panatier et al, 2011), both revealed using confocal microscopy, and astrocytic nodes and shafts within the spongiform structure visualized using live STED microscopy (Arizono et al, 2020).…”
Section: Tools To Dissect the Role Of Ip 3 R Isoforms Experimental And Analytical Toolsmentioning
confidence: 99%
“…To accurately capture Ca 2+ dynamics in sub-cellular compartments, there is a need to adopt imaging techniques with improved resolution and to develop tools for efficient analysis in three-dimensional (Bindocci et al, 2017;Romanos et al, 2019). Because of our poor understanding of functional compartments, analysis of astrocytic Ca 2+ dynamics has been moving toward state-of-the-art event-based analysis (Romanos et al, 2019;Wang et al, 2019;Bjørnstad et al, 2021), nevertheless ROI (regionof-interest) based analysis, informed by cellular anatomy (functional compartments) and molecular architecture, has been critical for understanding neuron physiology (e.g., spines and boutons). To this end, the identification of morphologically distinct subcellular compartments are promising targets for classical ROI based analysis, i.e., "glial microdomains" on Bergmann glial processes (Grosche et al, 1999) and "astrocytic compartments" on major branches (Panatier et al, 2011), both revealed using confocal microscopy, and astrocytic nodes and shafts within the spongiform structure visualized using live STED microscopy (Arizono et al, 2020).…”
Section: Tools To Dissect the Role Of Ip 3 R Isoforms Experimental And Analytical Toolsmentioning
confidence: 99%
“…Recently, several image analysis algorithms have been developed to quantify astrocyte calcium signals in 2D+time microscopy images. Among them, we can cite GECIquant [43], CaSCaDe [18], FASP [44], AQuA [45] and, more recently, Begonia [46] and Astral [47]. Most of these methods are ROI-based approaches (ROI: region of interest), meaning that calcium signals are analyzed through fixed spatial boundaries in the image.…”
Section: Imaging Methodsmentioning
confidence: 99%
“…Contrary to AQuA, however, Begonia allows for easy integration of other time-series data and is optimized for handling large, high-frame-rate ( ) datasets, thereby avoiding significantly long processing times. 124 …”
Section: Analysis Tools For Calcium Imaging Datamentioning
confidence: 99%
“…Contrary to AQuA, however, Begonia allows for easy integration of other time-series data and is optimized for handling large, high-frame-rate (∼30 Hz) datasets, thereby avoiding significantly long processing times. 124 Majority of the aforementioned analysis packages are targeted to single cell analysis. Software package Astral is designed to analyze astrocyte-astrocyte or astrocyte-neuron interactions at a network level.…”
Section: Imaging Calcium Dynamics In Astrocytesmentioning
confidence: 99%